2009
DOI: 10.1097/ta.0b013e31819634a1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Hemostatic Granules/Powders With Currently Deployed Hemostatic Products in a Lethal Model of Extremity Arterial Hemorrhage in Swine

Abstract: The new hemostatic agents are significantly more effective in treating arterial hemorrhage than currently deployed products. Among them, WS granules appear to be most efficacious, followed by SQR and CX powders. The clinical significance of tissue damage caused by these agents and any potential risk of embolism with procoagulant granular/powder products are unknown and warrant survival studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 10 publications
3
119
0
3
Order By: Relevance
“…observations from a separate study of hemostatic dressings, Kheirabadi et al reported that CBG was more effective than TMS in bleeding control and provided better bleeding control than the standard of care dressing (compressed gauze) (personal communication, [16]. Interestingly, they outlined the importance of the nature of the support material in gauze dressing property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…observations from a separate study of hemostatic dressings, Kheirabadi et al reported that CBG was more effective than TMS in bleeding control and provided better bleeding control than the standard of care dressing (compressed gauze) (personal communication, [16]. Interestingly, they outlined the importance of the nature of the support material in gauze dressing property.…”
Section: Discussionmentioning
confidence: 99%
“…Two injury models [6][7][8][9][10][11][12][13], a full femoral transection (including artery and vein) and a femoral artery puncture yield massive blood loss in the early phase of bleeding and severe hemorrhagic shock consequences if untreated. Our previous results indicated that dressing efficacy outcomes were different across these two injury models [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…B. am Hals, Abdomen oder in den Leisten [869][870][871][872][873]. Benutzen Sie bei stark blutenden äußeren Wunden, die durch direkten Druck allein nicht kontrollierbar sind oder deren Lage einen direkten Druck nicht zulassen, blutstillende Verbände [874][875][876][877].…”
Section: Blutstillende Verbändeunclassified
“…[1,6,7] The need for hemostatic agents is greater in the event of large-scale disaster such as terrorist attack, bombing, or devastating earthquake, though in such austere conditions, proper hemostasis of all those wounded is often impossible to achieve. [1][2][3][4][5][8][9][10][11][14][15][16]18,20] The aim of the present study was to test the hemostatic effect of chitosan linear polymer and compression, compared with standard gauze dressing and compression in an experimental young sheep model with severe bleeding of femoral artery and vein. The hypothesis was that chitosan linear polymer would stop the bleeding more quickly and effectively than the standard treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid hemostasis is essential as a strategy, not only for initial survival, but also for optimal recovery. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] A recent review of autopsies of 982 combat deaths from Iraq and Afghanistan revealed that nearly 24% could have been prevented with effective treatment. Of those potentially preventable deaths, 85% occurred as a result of hemorrhage, 1/3 of which were compressible, 2/3 of which were not, em-…”
mentioning
confidence: 99%